Gambling preferences and stock price crash risk: Evidence from China - Ji, Qiong; Quan, Xiaofeng; Yin, Hongying; Yuan, Qingbo (Journal of Banking & Finance, 2021)
This paper investigates whether attitudes towards gambling help explain the occurrence of stock price crashes in China. By using a province's per capita welfare lottery sales as a proxy for local gambling preference, we find that firms in regions with stronger gambling preference experience greater stock price crash risk. This result is robust to a battery of sensitivity tests after addressing possible endogeneity issues by using an instrumental variable approach and propensity score matching. Furthermore, we find that the impact of local gambling attitudes on stock price crash risk is mitigated by higher quality internal monitoring and more stringent external monitoring. Lastly, we identify two channels through which gambling preferences intensify stock price crash risk: aggressive corporate strategies and speculative accounting practices. Overall, these findings suggest that local gambling preferences influence firms’ stock price crash risk.